U-Shaped Intrapericardial Chronic Expanding Hematoma Due to Blunt Chest Trauma. (February 2021) - Ito, Hiromasa; Okamoto, Ryuji; Inagaki, Masahiro; Seko, Tetsuya; Kasai, Atsunobu; Tokui, Toshiya; Ito, Masaaki; Dohi, Kaoru
Abstract : Supplemental Digital Content is available in the text.